Toxoplasma Infection Alters Lipid Profiles Challenging Cardiovascular Norms: Infeksi Toksoplasma Mengubah Profil Lipid yang Menantang Norma Kardiovaskular - Qasim Ibrahim Khalaf (Academia Open, 2024)
This study conducted at Baquba Teaching Hospital from January to April 2024, investigated the lipid profiles of 75 participants (50 patients with Toxoplasma and 25 controls) aged between 50 and 60 years. Existing research suggests a potential link between Toxoplasma infection and alterations in lipid metabolism; however, specific effects on different lipid fractions are not well-understood. This study aimed to explore the association between Toxoplasma infection and changes in lipid profiles, particularly focusing on whether infection status correlates with variations in high-density lipoprotein (HDL) levels. Venous blood samples were collected pre-breakfast and processed to obtain serum, which was analyzed for lipid profiles. The findings indicated that lipid levels generally increased in Toxoplasma patients compared to controls, except for a decrease in HDL levels. These results suggest that Toxoplasma infection could influence lipid metabolism, potentially impacting cardiovascular risk. Further research is needed to understand the mechanisms underlying these changes and their clinical implications. Highlights: Toxoplasma infection is linked to significant changes in lipid profiles. The study identifies a unique decrease in HDL levels among infected individuals. Implications suggest potential cardiovascular risks associated with Toxoplasma. Keywords: Toxoplasma, Lipid Metabolism, Cardiovascular Risk, HDL Decrease